Improving the voltage quality of Abu Hummus network in Egypt - Ibrahim A. Nassar; Mohammed Sh. Seif; Mahmoud M. ElAttar (International Journal of Electrical and Computer Engineering (IJECE), 2020)
In this paper the performance of the electrical network of Egypt is studied by considering a small part on the network (Abu Hummus city). The transmission network of Abu Hummus city was created for 66 kV, 11 kV, and 0.4 kV in the digital simulation and electrical network calculation (DIgSILENT power factory software) to study the voltage profiles. The load flow operational analysis was performed to obtain the voltage magnitudes at every bus bar. The voltage magnitudes in 11 kV and 0.4 kV networks were 10% to 15% less than the nominal value due to overloading off the transmission lines and the voltage magnitudes in 66 kV was within permissible limits. By using automatic tap-changing transformer or Static VAR System, the main idea of this paper is to obtain the voltage profiles at every bus bar to improve the voltage quality of the networks, so as to achieve better voltage profiles on the low voltage side without much effect on high voltage side under various operating conditions.